Clairvoyance in the Perspective of Modern Science - Waheed, Palvasha (Pakistan Armed Forces Medical Journal, 2025)
Man has been fascinated by the phenomenon of “Clairvoyance” since ages. Whether one believes in its reality or not, one is still attracted to the possibility of seeing beyond the physical senses and obtaining help from unconventional and supernatural powers.The term “clairvoyance” comes from a combination of two French words; “Clair” meaning clear and “voyant” meaning vision. In other words, it refers to one’s ability to sense information without using any known sensory medium, hence the terms extrasensory perception (ESP), “sixth sense” etc. Clairvoyance or “Paranormal beliefs” relate to experiences that have not been scientifically analyzed or proven.1 A poll conducted in 2005 in United States of America, having a sample size of 1002, found that 55% subjects had faith in spiritual healing of the body through mind, 41% believed in ESP and 31% believed in the existence of mental telepathy.2